Immunological Analysis and Generation of Dendritic Cells From Lavage Fluid Obtained by Cell‐Free and Concentrated Ascites Reinfusion Therapy. Issue 3 (June 2017) - Ogasawara, Masahiro; Miyashita, Mamiko; Iida, Michio; Fukuhara, Takashi
Abstract: Cell‐free and concentrated ascites reinfusion therapy (CART) is an effective treatment for patients with refractory ascites. Cellular components such as cancer cells and blood cells are removed and discarded. The aim of this study was to investigate the alteration of immune cells in lavage fluid and the generation of dendritic cells (DCs) from lavage fluid obtained by CART. Flow cytometry analysis showed a trend toward immunosuppression and impairment in innate immunity in lavage fluid. Immature DCs with downregulation of CD14 and increased antigen‐uptake were generated by culturing monocytes obtained from lavage fluid with GM‐CSF and IL4. Following the culture with proinflammatory mediators, mature DCs with upregulation of CD83 and potent ability of T cell activation were induced. There were no significant phenotypical or functional differences between these DCs and DCs derived from peripheral blood, indicating lavage fluid might be employed for an alternative cellular source for the generation of DCs.